Evaluation of the Implementation Supplementary Feeding Program for Toddlers at the Dosay Community Health Center, Jayapura Regency in 2023 - Warisyu, Aksamina Demelda; Tingginehe, Rosmin Mariati; Irab, Semuel P.; Zainuri, Aguz; Hasmi, Hasmi; Bouway, Dolfinus (Formosa Journal of Science and Technology, 2024)
The aim of this research is to examine the evaluation of the supplementary feeding program for malnourished and malnourished toddlers from the input aspect, process aspect and output aspect in the Dosay Community Health Center Working Area, Jayapura Regency. The type of research used is descriptive using qualitative methods, with a case study approach. The results of this research state that in the input aspect there are still obstacles to financing. This is proven by the provision of optimal and innovative services by community health center officers to malnourished toddlers in providing local supplementary food, in addition to weighing toddlers' weights every time officers deliver food. The output of this activity has been achieved from the nutrition officer's report in December 2023 that as many as 5 (five) toddlers who took part in this program, in semesters 2 (two) and 3 (three) experienced weight gain and were declared to have returned to normal nutritional status.